Pengaruh Kualitas Laporan Keuangan, Debt Maturity, Kinerja Profitabilitas, Tax avoidance, dan CSR Performance Terhadap Efisiensi Investasi - Fika Putri Rahayu; Nur Diana; Irma Hidayati (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of the quality of financial statements, debt maturity, profitability performance, tax avoidance, and csr performance on investment efficiency in companies. Investment efficiency is an important indicator to assess the extent to which a company is able to generate profits from the investments made. This research is a quantitative research with secondary data sources using financial reports obtained through the official website of the Indonesia Stock Exchange (IDX) www.idx.co.id. The population in this study are mining companies listed on the Indonesia Stock Exchange for the 2018-2021. The data obtained will be calculated, tested and reprocessed against the proposed hypothesis using statistical applications. The results show that the quality of financial reports, debt maturity, profitability performance, tax avoidance, CSR performance simultaneously affect investment efficiency, financial report quality has a positive effect on investment efficiency, debt maturity has a negative effect on investment efficiency, profitability performance has a positive effect on investment efficiency, tax avoidance has no effect on investment efficiency, and csr performance has a positive effect on investment efficiency.Keywords: Quality of financial reports, debt maturity, profitability performance, tax avoidance, CSR performance, investment efficiency